2004
DOI: 10.1111/j.1442-2042.2004.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

The female partner's satisfaction with sildenafil citrate treatment of erectile dysfunction

Abstract: Background : Data on female partners' satisfaction are scarce, although there have been many articles on patient satisfaction after sildenafil citrate treatment. The aim of this study was to evaluate the satisfaction of female partners of patients receiving sildenafil citrate for their erectile dysfunction (ED) and to assess the female partners' sexual function. Methods : Ninety-eight patients with ED were treated. Their female partners were asked to answer a questionnaire we have prepared to evaluate the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 13 publications
1
29
0
2
Order By: Relevance
“…In that study, most of the subjects (66.7%) were satisfied, and 20% were not satisfied with the treatment with sildenafil. Besides, only 20% of the females' partners were worried about the side effects [32]. These findings were in line with those of the present study.…”
Section: Resultssupporting
confidence: 83%
“…In that study, most of the subjects (66.7%) were satisfied, and 20% were not satisfied with the treatment with sildenafil. Besides, only 20% of the females' partners were worried about the side effects [32]. These findings were in line with those of the present study.…”
Section: Resultssupporting
confidence: 83%
“…Published reports include surveys of partners of men being treated with a phosphodiesterase type 5 inhibitor for ED, 7,8 an open-label, prospective trial that assessed the sexual function of partners of men treated for ED with penile prosthesis implantation or sildenafil compared with that of partners of men without ED, 2 and pooled partner data from placebo-controlled sildenafil clinical trials of ED. 9 A prospective, double-blind, placebo-controlled trial showed improvement in scores on the erectile function domain of the International Index of Erectile Function (IIEF; P < 0.0001 versus placebo) in men treated with flexible-dose (5, 10, and 20 mg) vardenafil for ED; their partners showed significant improvement in scores for all domains of the Female Sexual Function Index (FSFI) except pain (P < 0.01 versus placebo).…”
Section: Introductionmentioning
confidence: 99%
“…Heiman et al 19 have reported that the EDITS Partner Index score of 85 female partners of sildenafil-treated men was 57.7, which is also compatible with our result of 57.2 (Table 3). Ichikawa et al 32 reported a satisfaction rate of 66.7% when using a new questionnaire for assessing female partners' satisfaction with sildenafil treatment for ED, which they developed.…”
Section: Pde5 Inhibitors For Erectile Dysfunction S-t Huang and B-p Jmentioning
confidence: 99%